The Idea of War in Russian Political Thought after 1991 - Diec, Joachim (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2023)
As time passed, in Russian political thought after the collapse of the Soviet Union, militarism or even an apology for war came to the fore. The aim of the study was to detect the most important models of this trend, taking into account the timeline of the Crimean events in 2014, and to attempt to explain its background in the absence of significant military threats to Russia from the international environment. Four main models of post-Soviet militarism have been distinguished: a) the rational model, pointing to the effects of military action in the modern world; b) the dualistic model of a clash between the traditionalist Russian civilization and the corrupt and expansionist West; c) the fatalistic concept of war as an inevitable aspect of the maturation of societies; d/the revivalist model, where war is treated as a device of social mobilization.

W miarę upływu czasu w rosyjskiej myśli politycznej po upadku Związku Radzieckiego w coraz większym stopniu dochodził do głosu militaryzm lub nawet apologia wojny. Zadaniem studium było wykrycie najważniejszych modeli tej tendencji z uwzględnieniem cezury czasowej wydarzeń krymskich 2014 roku, a także podjęcie próby wyjaśnienia jej podłoża przy braku istotnych czynników militarnego zagrożenia dla Rosji ze strony otoczenia międzynarodowego. Wyróżniono cztery główne modele militaryzmu postsowieckiego: a) racjonalny, ekspercki wskazujący na skutki podjęcia działań militarnych we współczesnym świecie; b) dualistyczny model zderzenia tradycjonalistycznej cywilizacji rosyjskiej z zepsutym i ekspansjonistycznym Zachodem; c) fatalistyczny koncept wojny jako nieuniknionego aspektu dojrzewania społeczeństw; d) model „odrodzeniowy”, gdzie wojna stanowi głównie środek mobilizacji społecznej.
Idea wojny w rosyjskiej myśli politycznej po roku 1991
Keywords: Russia; political thought; war; militarism; Rosja; myśl polityczna; wojna; militaryzm